Hairy cell leukemia 2018: Update on diagnosis, risk‐stratification, and treatment. Issue 12 (7th November 2017) - Troussard, Xavier; Cornet, Edouard
Abstract: Disease overview: Hairy cell leukemia (HCL) and HCL‐like disorders, including HCL variant (HCL‐V) and splenic diffuse red pulp lymphoma (SDRPL), are a very heterogeneous group of mature lymphoid B‐cell disorders, characterized by the identification of hairy cells, a specific genetic profile, a different clinical course and the need for appropriate treatment. Diagnosis: Diagnosis of HCL is based on morphological evidence of hairy cells, an HCL immunologic score of 3 or 4 based on the CD11C, CD103, CD123, and CD25 expression, the trephine biopsy which makes it possible to specify the degree of tumoral medullary infiltration and the presence of BRAF V600E somatic mutation. Risk stratification: Progression of patients with HCL is based on a large splenomegaly, leukocytosis, a high number of hairy cells in the peripheral blood and the immunoglobulin heavy chain variable region gene mutational status. VH4‐34 positive HCL cases are associated with poor prognosis Risk adapted therapy: Purine analogs (PNA) are indicated in symptomatic first line HCL patients. The use of PNA followed by rituximab represents an alternative option. Management of progressive or refractory disease: It is based on the use of BRAF inhibitors associated or not with MEK inhibitors, recombinant immunoconjugates targeting CD22 or BCR inhibitors.